Uso de K-10 e irradiação de microondas no estudo da metodologia de transesterificação e na síntese de β-enamino ésteres - Brauer, Martin Claudio Nin (2005)
Due to the high chemical versatility of β-keto esters and the β-enamino carbonylic compounds as synthetic precursors, our research group has investigated and developed methodologies for their synthesis and reactivity. In the present work, we aim to establish a methodology for the transesterification of β-keto esters using montmorillonite (K-10) as a support or catalyst by itself or together with microwave irradiation (MW). We used the methodology to evaluate the synthesis and reactivity of β-enamino esters. The cyclic β-keto ester ethyl-2-oxo-1-cyclopentanecarboxilate was synthesized by ethanol esterification followed by Dieckmann Cyclization of adipic acid. To obtain the series of the cyclic β-keto esters derived from ethyl-2-oxo-1-cyclopentanecarboxilate by transesterification reaction with allylic and benzylic alcohol and (1S, 2R, 5S)-(+)-menthol, montmorillonite (K-10) as catalyst with microwaves was used. To validate the methodology chosen for our work, we compared microwave irradiation to the use of reflux in toluene. The use of K-10/MW in the absence of solvent was shown to be more efficient than refluxing in toluene, giving higher yields with a much reduced reaction time. Cyclic β-enamino esters were obtained by condensation of the previously synthesized β-keto esters with primary amines, using the same K-10/MW methodology adapted to a sealed flask. This step gave excellent results. For the study of the β-enamino esters reactivity evaluation we tried several reduction systems for ethyl 2-allylamino-1-cyclopentene-1-carboxylate, without success. For the evaluation of the β-keto esters reactivity we chose ethyl 2-oxo-1-cyclopentanecarboxylate and allyl 2-oxo-1-cyclopentanecarboxylate. They were used in the condensation reaction with secondary amines and also for cyclization using Mn(OAc)3, to give a cyclic amide and a spiro compound, respectively.